3
$\begingroup$

I am studying my course on permutation representation, and I am stuck at understanding the left action of a finite group on the permutation representation $F(X,\Bbb C)$. In my course it is given for $(g,\phi)\in G\times F(X,\Bbb C) $ by:

$g*\phi(x\in X)\to \phi(g^{-1}x)$.

Is this a left group action?

I have: $h*(g*\phi(x))= h*\phi(g^{-1}x)= \phi(h^{-1}g^{-1}x) = \phi((gh)^{-1}x)= (gh)*\phi(x) \neq (hg)*\phi(x)$.

I must be missing something.

$\endgroup$
7
$\begingroup$

Note that by the definition $g*\phi$ is in $F(X,\mathbb C)$ defined by $(g*\phi)(x):= \phi(g^{-1}x)$, so the calculation is the following: $$\begin{align} (h*(g*\phi))(x)&= (g*\phi)(h^{-1}x)\\ &= \phi(g^{-1}h^{-1}x)\\ &= \phi((hg)^{-1}x)\\ &= (hg*\phi)(x). \end{align}$$ Thus $h*(g*\phi)= hg*\phi$.

$\endgroup$
1
$\begingroup$

In addition to the accepted answer I want to point out that one can also start by substituting the inner expression. Since $(g*\phi)(x) := \phi(g^{-1}x)$, we have $g*\phi = x \to \phi(g^{-1}x)$, therefore

$$\begin{align} (h*(g*\phi))(x) &= (h*(t\to\phi(g^{-1}t)))(x)\\ &= (t\to\phi(g^{-1}t))(h^{-1}x)\\ &= \phi(g^{-1}(h^{-1}x))\\ &= (hg*\phi)(x). \end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.